2019
DOI: 10.3390/app9235069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooling Conditions on Microstructure and Mechanical Properties of Friction Stir Welded Butt Joints of Different Aluminum Alloys

Abstract: The aim of this work is to evaluate the difference between the properties of several aluminum alloy joints welded with the traditional air-cooled friction stir welding process and others obtained by the combination of the traditional friction stir welding setup with a water-cooling system. In particular, precipitation-hardening alloys AA2024-T3, AA6082-T6 and AA7075-T6, and a work-hardening alloy, AA5754-H111, were taken into account. From Rockwell and Vickers hardness maps, it was possible to observe a clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Considering these combinations, it is possible to observe that cooling with water is the preferred solution; the only exception is for the AA2024. This piece of evidence agrees with what emerged from previous studies on the effects of the cooling solution on the microstructure of FSW joints 9,50 where it has been shown that the AA2024 is the least affected material by the water cooling. Subsequently, the welds were realized to verify the developed approach reliability defining a benchmark between the forecasted outputs and the experimental UTS and hardness in different areas of the joint.…”
Section: Fsw Process Optimization Through Psosupporting
confidence: 92%
“…Considering these combinations, it is possible to observe that cooling with water is the preferred solution; the only exception is for the AA2024. This piece of evidence agrees with what emerged from previous studies on the effects of the cooling solution on the microstructure of FSW joints 9,50 where it has been shown that the AA2024 is the least affected material by the water cooling. Subsequently, the welds were realized to verify the developed approach reliability defining a benchmark between the forecasted outputs and the experimental UTS and hardness in different areas of the joint.…”
Section: Fsw Process Optimization Through Psosupporting
confidence: 92%
“…For the FWSed specimens, only the ultimate tensile strength (UTS) is reported, because it was not possible to evaluate the yield strength (YS) owing to the localization of the plastic straining of the specimens in the TMAZ/HAZ zone. The decrease in the mechanical properties at the thermomechanical and heat affected zones is the result of the modification in the microstructure of the alloy, with solubilization and reprecipitation of the straightening second phases, as reported in previous works by authors [10,14,18,22,24]. A good reproducibility was observed in the tensile strength of the FSWed joints, thus confirming the absence of macroscopic defects alongside the weld.…”
Section: Preparation Of the Weldssupporting
confidence: 83%
“…The zones close to the nugget, which has the microstructure altered both by the action of the mechanical straining and the thermal effect, is called thermo-mechanically affected zone (TMAZ); after this zone, moving away from the nugget toward the base metal, there is an area that has not 2 of 16 undergone mechanical straining, but only heating and therefore it is called heat-affected zone (HAZ). The microstructure and extension of these zone, nugget, TMAZ, and HAZ, depend on the size and shape of the pin, the thickness of the sheet, and the welding parameters, in particular the force exerted on the pin, its rotation speed, and feed rate [9,10]. Depending on the tool rotation side, "advancing side" and "retreating side" are defined [11].…”
Section: Introductionmentioning
confidence: 99%
“…Peak temperature, incubation time, and stir action are the vital parameters that determine the evolution of IMCs. 53 When FSW is carried out in the actively cooled and vibrated environments, IMCs in the stir zone are no longer a concern, as their evolution is highly restricted due to the lower peak temperature and higher stir action. The vibration breaks the IMC layer into small parts with uniform distribution in the weld zone.…”
Section: Mechanical Properties and Fracture Surface Analysismentioning
confidence: 99%